1988
DOI: 10.1152/jappl.1988.65.6.2726
|View full text |Cite
|
Sign up to set email alerts
|

Targeted resistive ventilatory muscle training in chronic obstructive pulmonary disease

Abstract: To overcome the problem of altered breathing strategy during resistive ventilatory muscle training (VMT), we used a single-orifice inspiratory resistance together with a target feedback device (TFD) in patients with chronic obstructive pulmonary disease (COPD). In a preliminary study (study A), we showed that the resistance plus TFD was effective in controlling breathing strategy. We subsequently used the resistor plus TFD in a 5-wk study (study B) of VMT in 17 COPD patients who were randomized into high-inten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
103
1
5

Year Published

1991
1991
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 102 publications
(113 citation statements)
references
References 19 publications
4
103
1
5
Order By: Relevance
“…In Group 2 only 3 patients increased their IMPO and it was due to an increment in both factors. These results are in agreement with those reported by BELMAN and SHADMEHR [10], who also showed that IMT increases Vmax.…”
Section: Discussionsupporting
confidence: 94%
See 4 more Smart Citations
“…In Group 2 only 3 patients increased their IMPO and it was due to an increment in both factors. These results are in agreement with those reported by BELMAN and SHADMEHR [10], who also showed that IMT increases Vmax.…”
Section: Discussionsupporting
confidence: 94%
“…In agreement with previous reports [9][10][11][12][13][14], our study confirms that the magnitude of the load used for inspiratory muscle training is a critical determinant of the results in patients with CAL; with an adequate load, IMT has a favourable effect on inspiratory muscle function, dyspnoea and physical capacity. Our study also shows that maximal inspiratory muscle power output is useful for evaluating the effects of training, and that patients can develop a strategy to cope with respiratory loads without reaching the critical area of inspiratory muscle fatigue [18].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations